2018
DOI: 10.29252/johe.7.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low back pain and its associated factors among physiotherapists in Dhaka city of Bangladesh in 2016

Abstract: Article InfoBackground: Low back pain (LBP) is one of the major public health issues among health care professionals, especially among the physiotherapists. The aim of this study was to determine the prevalence of LBP among Bangladeshi physiotherapists and its associated factors. Materials and Methods: A cross-sectional study was conducted among 130 physiotherapists practicing in Dhaka city. Hospitals, clinics and private chambers, and the respondents were selected conveniently (on invitation those who were ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…3 In Bangladesh, the prevalence of LBP ranges between 18.6-60.8%. [6][7][8][9] Instruments An online, standardized, self-administrated questionnaire 27 was used for data collection. The questionnaire was in English language and had three sections.…”
Section: Introductionmentioning
confidence: 99%
“…3 In Bangladesh, the prevalence of LBP ranges between 18.6-60.8%. [6][7][8][9] Instruments An online, standardized, self-administrated questionnaire 27 was used for data collection. The questionnaire was in English language and had three sections.…”
Section: Introductionmentioning
confidence: 99%
“…3 In Bangladesh, the prevalence of LBP ranges between 18.6-60.8%. [6][7][8][9] Instruments An online, standardized, self-administrated questionnaire 27 was used for data collection. The questionnaire was in English language and had three sections.…”
Section: Introductionmentioning
confidence: 99%
“…Mondal et al reported that three in every five physiotherapists in Bangladesh suffer from LBP. 7 That showed that the people involved in the health sector are at higher risk of developing LBP. Hence, it is essential to conduct more studies to determine the prevalence and risk factors of LBP among health science students and health professionals in Bangladesh so that the results can be compared to know the exposure better, which will help to take necessary initiatives to lessen its impact.…”
Section: Introductionmentioning
confidence: 99%
“…4 LBP prevalence is also high in middle and low-income countries, 5 including Bangladesh. [6][7][8][9] Nearly 97% of patients have LBP due to mechanical factors, while 2% are due to visceral disease and 1% non-mechanical reasons. 10,11 Intervertebral disc herniation is the most common cause of LBP in adults, and that accounts for 4% of mechanical LBP.…”
Section: Introductionmentioning
confidence: 99%